1999
DOI: 10.1007/bf03161687
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of wetland regulation through hydrogeomorphic classification and landscape profiles

Abstract: Landscape profiles describing the pattern of the diversity of wetlands in a region can serve as a standard for characterizing the resource and quantifying the effects of management decisions. We used hydrogeomorphic (HGM) classification to generate landscape profiles to evaluate the effects of mitigation in the rapidly urbanizing area of Portland, Oregon, USA. The profiles were produced from information on the types, numbers, and relative abundances of wetlands by HGM class. Using field data, topographic maps,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 21 publications
1
40
0
Order By: Relevance
“…However, as noted by Cairns and Heckman (1996) this immediately raises the question as to what frame of reference or benchmark does one use to establish the pre-disturbance condition? Moreover, others have demonstrated that restoring an ecosystem to a prescribed composition is difficult because the assumption of predictable community assembly is often not valid and restoration can result in unpredictable outcomes (Gwin et al 1999;Magee et al 1999;Zedler 2000;Magee and Kentula 2005). Such results led Hilderbrand et al (2005) to go so far as to declare such prescriptive restoration approaches to be a so-called restoration myth (i.e., their "Carbon Copy" myth) in that creating or restoring an ecosystem that is a copy of an idealized state with a single endpoint is at odds with the dynamic nature of ecosystems.…”
mentioning
confidence: 98%
“…However, as noted by Cairns and Heckman (1996) this immediately raises the question as to what frame of reference or benchmark does one use to establish the pre-disturbance condition? Moreover, others have demonstrated that restoring an ecosystem to a prescribed composition is difficult because the assumption of predictable community assembly is often not valid and restoration can result in unpredictable outcomes (Gwin et al 1999;Magee et al 1999;Zedler 2000;Magee and Kentula 2005). Such results led Hilderbrand et al (2005) to go so far as to declare such prescriptive restoration approaches to be a so-called restoration myth (i.e., their "Carbon Copy" myth) in that creating or restoring an ecosystem that is a copy of an idealized state with a single endpoint is at odds with the dynamic nature of ecosystems.…”
mentioning
confidence: 98%
“…Thus, as a wetland landscape varies in scale, due perhaps to conversion, draining or other human-induced disturbances, the impact on the provision of and synergies between wetland services can be substantial. Such a landscape approach is being used increasingly for assessing the cumulative effects of wetland loss and degradation, characterizing wetland boundaries and identifying restoration or mitigation opportunities (NRC 1995, Bedford 1996, 1999, Gwin et al 1999, Mitsch and Gosselink 2000, Simenstad et al 2006. It follows that the various goods and services provided by a wetland will also be tied to, and thus defined by, its landscape extent; i.e.…”
Section: Maintenance Of Temperature Precipitationmentioning
confidence: 99%
“…Increasingly, a hydrologybased landscape approach is being used to assess the cumulative effects of wetland loss and degradation, characterizing wetland boundaries and identifying restoration or mitigation opportunities (Bedford 1996, 1999, Gwin et al 1999, Mitsch and Gosselink 2000, NRC 1995, Simenstad et al 2006. As emphasized in this paper, such an approach is consistent with the view of wetlands as natural assets that generate multiple ecosystem services.…”
Section: Final Remarksmentioning
confidence: 99%
“…As management activities change the numbers, types, and positions of wetlands on the landscape, especially in urban areas (e.g., Kentula et al 1992a, b, Holland et al 1995, Bedford 1996, Gwin et al 1999, maintaining the diversity of hydrologic regimes will be essential to preserving the diversity of wetland functions. Bedford (1996) has recommended landscape-level analyses of wetlands to assess the cumulative effects of past management decisions and to guide future management decisions toward preserving and restoring the natural mosaic.…”
Section: Introductionmentioning
confidence: 99%